AUTOMOBILE ENTERPRISES EVALUATION OF EFFICIENCY OF INNOVATIVE BENCHMARKING SYSTEM (ResearchJet Journal of Analysis and Inventions, 2023)
The article describes the factors determining the innovative benchmarking potential of automotive enterprises, the algorithm for developing and evaluating the benchmarking potential of automotive enterprises, the formulas for assessing the innovative benchmarking potential of automotive enterprises.